Study of Linear Optical Properties of Acridine-orange Laser Dye - Lazem Hassan Aboud (Journal of Global Pharma Technology, 2016)
In this research, the linear optical properties and the effect of concentration of the solution on absorption spectra and fluorescence spectra of the acridine_orange dye. It was prepared three concentrations acridine_orange dye dissolved in ethanol (1*10^-3, 1*10^-4, 1*10^-5) M. It was measured spectroscopic properties of the dye solution and for all concentrations (absorption coefficient, refractive index, and fluorescence life-time and quantum yield of florescence level). The results showed that the linear absorption coefficient and linear- refractive index increase with solution concentration increasing and (life-time of fluorescence increases, quantum yield decreases) with solution concentration increasing.Keywords: Acridine_orange dye, linear optical properties, laser dye.